(untitled) (The Toro Historical Review, 2024)
Welcome to volume 15, issue 2 of The Toro Historical Review! This issue features seven essays produced in upper-division history classes and represents remarkable achievements in undergraduate research, writing, and editing. Well done all! Congratulations to the authors: Mandeline Arguelles, Ana Canales-Molina, Samantha Chavez, Lauren Heib, Ava Kostka, Teresa Ornedo, and Alexis Verduzco And a special thank you to our editorial team who has worked hard to bring this issue to fruition. Thank you!